The influence of parental burnout on middle school students’ academic achievement: moderated mediation effect - Peng, Lingyi; Chen, Huohong; Peng, Jinhai; Liang, Wei; Li, Mengfang; Fu, Weifeng (Frontiers in Psychology, 2025)
IntroductionThis study investigates the influence of parental burnout on the academic achievement of middle school students, as well as the mediating role of academic self-efficacy and the moderating role of middle school students’ gender and parental gender.MethodsUtilizing a parent-child matched-pair design, a questionnaire survey was conducted with 738 middle school students and their parents (either fathers or mothers).ResultsThe findings revealed that: (1) parental burnout significantly and negatively predicted middle school students’ academic achievement; (2) academic self-efficacy partially mediated the relationship between parental burnout and middle school students’ academic achievement; and (3) the gender of middle school students moderated the initial segment of this mediating effect, while parental gender did not significantly moderate the relationship, indicating that the significant negative predictive effect of parental burnout on academic self-efficacy was evident only among female middle students.DiscussionThese results not only enhance our understanding of the mechanisms and conditions under which parental burnout impacts middle school students’ academic achievement, but also have important implications for improving middle school students’ academic self-efficacy and overall academic performance.